The Free Alpha-Hemoglobin: A Promising Biomarker for β-Thalassemia - Uday Younis, Hussein; Ahmed Ghazi, Faisal; Atif, Amin Baig (2014)
The purpose is to review the current knowledge and methods of determination of the free alpha hemoglobin with emphasis on its potential implications in patients with beta-thalassemia (β-thal).The severity of β-thal correlates with the extent of imbalance between α- and non-α-globin chains and the amount of the free alpha hemoglobin (free α- Hb) pool in the erythrocytes. To date, there is a lack of biomarkers that convey diagnostic and prognostic values in β-thal. Our ongoing research is aimed to evaluate the potential prognostic and diagnostic implications of free α-Hb to improve the care of patients with β-thal. Our ongoing research is aimed to quantify the free α-Hb for its potential prognostic and diagnostic implications towards improving the care of patients with various β-thal types in the years to come.